Pembuatan Bio Oil Dari Kayu Cemara Laut (Causarina Equisetifolia L) Dengan Teknologi Pirolisis Menggunakan Katalis Ni/NZA - Rahmansyah Rahmansyah; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The fundamental problem of national energy today is the tendency of fossil energy consumption increasing, which is not offset by the availability of fossil energy itself. So that the necessary strategic steps to face the energy challenge in the future with the development of renewable energy. One of them by converting biomass into bio oil through pyrolysis technology with the aid of a catalyst. The aims of this research was to produce bio oil from casuarina wood (Causarina equisetifolia L), knowing the physical and chemical characteristics of the bio oil from casuarina wood, determine the effect of supported Ni metal on resulting yield bio oil. Pyrolysis process uses 50 grams of casuarina wood (-100+200 mesh), the catalyst Ni/NZA with metal variation (0%, 2%, 3% w/w) and the variation amount (2%, 3%, 4% w/w), silinap 500 ml, carried out at a temperature 320 0C, stirring speed of 300 rpm by flowing nitrogen gas. The highest yield obtained on 2% of uses catalyst and 3% of Ni metal of 58,058%. Characteristics of the resulting bio oil, in the form of density 1,001 gr/mL, 6,761 cSt viscosity, acid number 17,760 mg NaOH/gr, and the flash point 48 oC.Keywords: bio oil, Causarina equisetifolia wood, Ni/NZA catalyst, pyrolysis